Cholesterol modulates the dimer interface of the beta(2)-adrenergic receptor via cholesterol occupancy sites - Prasanna, Xavier; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2014)
The beta(2)-adrenergic receptor is an important member of the G-protein-coupled receptor (GPCR) superfamily, whose stability and function are modulated by membrane cholesterol. The recent high-resolution crystal structure of the beta(2)-adrenergic receptor revealed the presence of possible cholesterol-binding sites in the receptor. However, the functional relevance of cholesterol binding to the receptor remains unexplored. We used MARTINI coarse-grained molecular-dynamics simulations to explore dimerization of the beta(2)-adrenergic receptor in lipid bilayers containing cholesterol. A novel (to our knowledge) aspect of our results is that receptor dimerization is modulated by membrane cholesterol. We show that cholesterol binds to transmembrane helix IV, and cholesterol occupancy at this site restricts its involvement at the dimer interface. With increasing cholesterol concentration, an increased presence of transmembrane helices I and II, but a reduced presence of transmembrane helix IV, is observed at the dimer interface. To our knowledge, this study is one of the first to explore the correlation between cholesterol occupancy and GPCR organization. Our results indicate that dimer plasticity is relevant not just as an organizational principle but also as a subtle regulatory principle for GPCR function. We believe these results constitute an important step toward designing better drugs for GPCR dimer targets.

Cholesterol-dependent conformational plasticity in GPCR dimers - Prasanna, Xavier; Sengupta, Durba; Chattopadhyay, Amitabha (Scientific Reports, 2016)
The organization and function of the serotonin1A receptor, an important member of the GPCR family, have been shown to be cholesterol-dependent, although the molecular mechanism is not clear. We performed a comprehensive structural and dynamic analysis of dimerization of the serotonin1A receptor by coarse-grain molecular dynamics simulations totaling 3.6 ms to explore the molecular details of its cholesterol-dependent association. A major finding is that the plasticity and flexibility of the receptor dimers increase with increased cholesterol concentration. In particular, a dimer interface formed by transmembrane helices I-I was found to be sensitive to cholesterol. The modulation of dimer interface appears to arise from a combination of direct cholesterol occupancy and indirect membrane effects. Interestingly, the presence of cholesterol at the dimer interface is correlated with increased dimer plasticity and flexibility. These results represent an important step in characterizing the molecular interactions in GPCR organization with potential relevance to therapeutic interventions.

Conformational dynamics of GPCR dimers is dependent on membrane cholesterol - Sengupta, Durba; Prasanna, Xavier; Chattopadhyay, Amitabha (Biophysical Journal, 2016)

Chapter 5: Experimental and computational approaches to study membranes and lipid-protein interactions - Sengupta, Durba; Kumar, G. Aditya; Prasanna, Xavier; Chattopadhyay, A. (Computational biophysics of membrane proteins, 2017)
Biological membranes are complex two-dimensional, non-covalent assemblies of a diverse variety of lipids and proteins. A hallmark of membrane organization is varying degrees of spatiotemporal heterogeneity spanning a wide range. Membrane proteins are implicated in a wide variety of cellular functions, and comprise ∼30% of the human proteome and ∼50% of the current drug targets. Their interactions with membrane lipids are recognized as crucial elements in their function. In this article, we provide an overview of experimental and theoretical approaches to analyze membrane organization, dynamics, and lipid-protein interactions. In this context, we highlight the wide range of time scales that membrane events span, and approaches that are suitable for a given time scale. We discuss representative fluorescence-based approaches (FRET and FRAP) that help to address questions on lipid-protein and protein-cytoskeleton interactions in membranes. In a complimentary fashion, we discuss computational methods, atomistic and coarse-grain, that are required to address a given membrane problem at an appropriate scale. We believe that the synthesis of knowledge gained from experimental and computational approaches will enable us to probe membrane organization, dynamics, and interactions at increasing spatiotemporal resolution, thereby providing a robust model for the membrane in health and disease.